Determinants and Performance of Regional Development Planning: Evidence from Nduga Regency - Hariman Usman; Elsyan R. Marlissa; Transna Putra Urip (LPPM STIE KRAKATAU, 2026)
Purpose: This study examines the factors influencing regional development planning performance in Nduga Regency, focusing on the contribution of planning document consistency, integration, and quality (RPJMD, RKPD, Renstra OPD, and Renja) to overall performance. Research Methodology: A quantitative approach was used, with primary data collected through structured questionnaires from 56 respondents across 28 regional government organizations in Nduga Regency. Data were analyzed using structural equation Modelling (SEM-PLS) with WarpPLS 8.0 software. Results: Internal factors—document quality, process effectiveness, resource commitment, and implementation readiness—had a significant positive effect on planning performance (P<0.01; R²=0.608; f²=0.608, large effect). External factors had a positive but non-significant effect (P=0.08; R²=0.179; f²=0.179, medium effect). Planning document consistency and quality contribute significantly to performance but underperform because of a disconnect between planning documents and budgeting instruments. Conclusions: Internal capacity and document alignment are key determinants of planning performance. Despite challenges such as geographical isolation and security disruptions, the main issue lies in limited human resource competence and weak coordination between planning and budgeting in the health sector. Limitations: The study's sample size is relatively small, consisting of only 56 respondents from 28 regional government organizations, which may limit the generalizability of the findings of this study. Additionally, the research focuses solely on Nduga Regency, a single urban area, and may not fully reflect the diverse challenges faced by other regions in the country. The study also did not account for potential biases in the data collection process, such as respondent perception or external variables not included in the model. Contribution: This is the first SEM-PLS study on regional planning performance in Nduga Regency, offering insights into the impact of internal constraints on planning in such regions.